Al-Qand fī dhikr ʿulamāʾ Samarqand - al-Nasafī, Najm al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Arabic literary tradition, biographies form a class of their own and have always been widely used. Whether about a single person or about some group, their shared objective was to provide an authoritative account of someone's lineage, social or literary career, academic or religious background or affiliation, or connection to some historic event. As examples one could mention Ibn Hishām's (d. 218/834) Sīrat Muḥammad rasūli ʼllāh , Ibn Abī Uṣaybiʿa's (d. 668/1270) Kitāb ʿuyūn al-anbāʾ fī ṭabaqāt al-aṭibbāʾ , or Nūr al-Dīn al-Ṭūkhī's (d. ca 900/1494) Quḍāt Miṣr . The author of the present work, Najm al-Dīn al-Nasafī (d. 537/1142-43), was a long-time resident of Samarqand and widely known and respected as jurist. He wrote more than 30 works, in Persian and in Arabic. The present volume contains an inventory of ḥadīth scholars bearing some connection to Samarqand. Its importance lies mainly in the many names of people, places, and books which are otherwise entirely unknown.